#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.

Click to Chat

1800-1023-196

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# if roots of (x-p)(x-q) = c are a and bwhat will be the roots of (x-a)(x-b) = -c please explain

## 3 Answers

8 years ago

Ans:p,q

Solution: (x-p)(x-q)-c=0 has roots a and b=> ab=pq-c & a+b=p+q;

similarly if s and t be the roots of (x-a)(x-b)=-c=>st=ab+c & s+t=a+b;(now wkt ab=pq-c=>st=pq)

therfore, s and t are p and q.  8 years ago

the answer is p and -q since in the first equation on equating we get a=c+b and b=c+q when we equate we get a-b=p-q which imples root of equaton 2 is p and -q

8 years ago

(x-p)(x-q)=c

x2-(p+q)x-c=0

hence,           a+b=p+q

and               a.b=pq-c

a.b+c=p.q

by solving other eq we get

x2-(a+b)x+ab+c=0

thus        sum of roots=a+b=p+q

product of roots=a.b+c=p.q

hence its roots are pand q

## ASK QUESTION

Get your questions answered by the expert for free